Project-based Learning: A Case Studying the Catholic Monarchs in Elementary Education - José Manuel Sáez López (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThis study aimed to assess the use of Project-Based Learning (PBL) in classroom practice with 121 primary school students in five different schools in Spain, analyzing the advantages and effectiveness of practicing PBL in social sciences, in the topic of the history of the Catholic Monarchs. In this pedagogical design, students interact and create their history-related content. The first dimension, PBL in the Catholic Kings unit comprises a quasi-experimental approach through a student t-test, which showed significant improvement regarding curriculum concepts and academic results. The second dimension, Assessment of elements and implementation of PBL, details data from 46 teachers and professors who evaluate the implementation and characteristics of PBL in the proposal and practice. From the results, the methodological approach using PBL improves academic results and encourages students to have a bigger role in the learning process, with active participation where students seek information, interact with classmates in groups, try to solve problems and create final products for subsequent presentations.Keywords: active learning; K-12; team teaching; project-based learning. AbstrakPenelitian ini bertujuan untuk menilai penggunaan Pembelajaran Berbasis Proyek (PBL) dalam praktik kelas dengan 121 siswa sekolah dasar di lima sekolah berbeda di Spanyol, menganalisis keuntungan dan efektivitas praktik PBL dalam ilmu sosial, dalam topik sejarah Monarki Katolik. Dalam desain pedagogis ini, siswa berinteraksi dan membuat konten mereka sendiri yang berkaitan dengan sejarah. Dimensi pertama, PBL dalam Kerajaan Katolik terdiri dari pendekatan kuasi-eksperimental melalui uji-t siswa, yang menunjukkan peningkatan signifikan terkait konsep kurikulum dan hasil akademik. Dimensi kedua, Penilaian elemen dan implementasi PBL, merinci data dari 46 guru dan profesor yang mengevaluasi implementasi dan karakteristik PBL dalam proposal dan praktik. Dari hasil penelitian disimpulkan bahwa pendekatan metodologis menggunakan PBL meningkatkan hasil akademik dan mendorong siswa untuk memiliki peran yang lebih besar dalam proses pembelajaran, dengan partisipasi aktif di mana siswa mencari informasi, berinteraksi dengan teman sekelasnya dalam kelompok, mencoba memecahkan masalah dan membuat produk akhir untuk presentasi selanjutnya.Kata kunci: pembelajaran aktif, K 12, pengajaran kelompok, pembelajaran berbasis proyek.